ASSESSING COMPANY VALUATION AND SPLIT SHAREHOLDER ANALYSIS FOR E-COMMERCE SHOPEE - Octafiany, Armita
Indonesia is the third largest contributor to the number of internet users in Asia, amounting to 7.4% with several users of 273,523,615 people. The background of technological advances and the number of internet users that continues to increase rapidly makes opportunities for a startup in e-commerce to develop very wide open. One of them is Shopee. To execute a startup business idea, of course it takes several costs that are not small. Sources of startup company funding itself can be obtained from various alternative capital sources that can increase the startup's growth potential. Shopee still relies on funding from their group company in the head quarter, Sea Ltd. With the large number of business lines run by Sea Ltd, large losses that still incurred by Shopee, and stock-market volatility, it's a good idea for Shopee Indonesia to start considering on getting funding from other investors. DCF and Venture Capital from Damodaran can be used as the possible valuation methods. In Venture Capital, it begins by estimating the expected earnings or revenues in a future year, but not too far into the future: two to five years is the typical range. Then venture capitalists receive a proportion of the business in return for the capital they bring to the firm. For DCF, this method is an improvement of the DCF method by using a top-down or bottom-up approach. After calculating the valuation using the venture capital method, it is found that the post money valuation would be $1,339.73 Million. With those numbers, it can be found that the proportional share of equity would be 44% from outside investor, and the rest 56% would be still from Sea Group as their parent company. For DCF Top Down approach method, it is found that the post money valuation would be $1,495.89 Million. With those numbers, it can be found that the proportional share of equity would be 39% from outside investor, and the rest 61% would be still from Sea Group as their parent company.